Evaluation of failure mechanism in lap splices and role of stirrup confinement using 3D RBSM. (1st February 2022) - Farooq, Usman; Nakamura, Hikaru; Miura, Taito
Highlights: A beam element-based 3D RBSM method is applied to study lap splices. Bond and failure mechanism of lap splices is evaluated based on various parameters. Failure mechanism of stirrup confinement is particularly highlighted. Abstract: The bond behavior and failure mechanisms of lap splices with multiple deformed rebars were evaluated using a Three-Dimensional Rigid Body Spring Model (3D RBSM) with beam element. Previous studies have shown the applicability of the method in simulating the bond behavior of single deformed rebar. In this study, we validated the applicability of the numerical method in the simulation of bond stress-slip behavior in unconfined and confined lap splices with various parameters. Then, in unconfined lap splices, we investigated the simulated detail internal crack development considering the strut crack propagation between the individual rebar of lap splices and around the rebars, phenomena that cannot be observed in test. It was found that at the failure section, the strut cracks interlink and propagate at an incline relative to the side surfaces, causing significant bond and concrete stress loss in the lap splice span. As a result, we investigated the failure mechanism and the roles of the geometric and material characteristics of stirrups in improving the performance of lap splices.